Genomic Analysis and Lineage Identification of SARS-CoV-2 Strains in Migrants Accessing Europe Through the Libyan Route - Tramuto, Fabio; Reale, Stefano; Lo Presti, Alessandra; Vitale, Francesco; Pulvirenti, Claudio; Rezza, Giovanni; Vitale, Fabrizio; Purpari, Giuseppa; Maida, Carmelo Massimo; Zichichi, Salvatore; Scibetta, Silvia; Mazzucco, Walter; et al. (Frontiers in Public Health, 2021)
Many African countries, representing the origin of the majority of refugees, asylum-seekers and other migrants, towards regions bordering on the Mediterranean area, are experiencing sustained local transmission of SARS-CoV-2. Sicily is one of the main entry gates of migrants crossing into Europe. We conducted a pilot study, based on the full-genome sequencing of SARS-CoV-2 strains isolated from migrants coming to Sicily by crossing the Mediterranean Sea, with the aim to investigate the viral genome polymorphism and to describe their genetic variations and the phylogenetic relationships. On the 21st of June, a non-governmental organization vessel rescued 210 migrants crossing the Mediterranean Sea from Libya to Sicily. Of them, 13.4% tested positive for SARS-CoV-2. Eighteen whole genome sequences were obtained to explore viral genetic variability. All but one of the sequences clustered with other viral African strains within the lineage A, whereas only one intermixed among B.1 lineage genomes. Our findings documented that most of the investigated migrants acquired SARS-CoV-2 infection before landing in Sicily. However, SARS-CoV-2 transmission during travel or in overcrowded Libyan immigrant camps and/or illegal transport boats could not be ruled out. SARS-CoV-2 molecular surveillance on migrants arriving to Europe through the Sicilian gate may improve the knowledge of global SARS-CoV-2 transmission dynamic also in light of the emergence of new variants.